(untitled) (Research, Society and Development, 2020)
The aim of this study was identify how occur the pesticides management used in grain cultivate and its relationship with health and environment in Santa Catarina Plateau region. Seventy-nine farmers that cultivate grains (soybean, corn and bean) were interviewed to collect information about sociodemographic data and of your rural property, use, transport, storage and disposal of pesticides wastes. Almost half of farmers do the pesticides transport in closed car, with other products and does not have an exclusive place to storage de pesticides. Besides, 26.6% do not receive technical assistance, 25.3% buy pesticides without prescription and 5.1% do not perform reverse logistics of empty containers. It was used 40 different types of pesticides in grain cultivate, being the glyphosate the herbicide most used, follow by the fungicide propinebe and insecticide acephate. In view of the agriculture model based in monoculture that imposes farmer’s use of pesticides, the results of this study can be considered a public health problem once the transportation, storage, and specially the inappropriately dispose of residues and empty containers can cause contamination on several environmental compartment, as well, the human health.